Hominin diversity in East Asia during the Middle Pleistocene: A premolar endostructural perspective. Issue 148 (November 2020) - Pan, Lei; Dumoncel, Jean; Mazurier, Arnaud; Zanolli, Clément
Abstract: Following the recent studies of East Asian mid-Middle to early Late Pleistocene hominin material, a large spectrum of morphological diversity has been recognized and the coexistence of archaic (' Homo erectus -like') and derived ('modern-like') dental morphological patterns has been highlighted. In fact, for most of these Chinese fossils, generally categorized as 'archaic Homo sapiens ' or 'post- H. erectus Homo', the taxonomic attribution is a matter of contention. With the help of μCT techniques and a deformation-based 3D geometric morphometric approach, we focused on the morphological variation in the enamel–dentine junction (EDJ) of 18 upper and lower premolars from Chinese Middle Pleistocene hominins. We then compared our results with a number of fossil and modern human groups, including Early Pleistocene H. erectus from Sangiran; late Early Pleistocene hominins from Tighenif, Algeria; classic Neanderthals; and modern humans. Our results highlight an evolutionary/chronological trend of crown base reduction, elevation of EDJ topography, and EDJ surface simplification in the hominin groups studied here. Moreover, this study brings insights to the taxonomy/phylogeny of 6 late Middle Pleistocene specimens whose evolutionary placement has been debated for decades. Among these specimens, Changyang premolars show features that can be aligned with the Asian H. erectus hypodigm, whereas Panxian Dadong and Tongzi premolars are more similar to Late Pleistocene Homo . Compared with early to mid-Middle Pleistocene hominins in East Asia, late Middle Pleistocene hominins evince an enlarged morphological variation. A persistence of archaic morphotypes and possible admixture among populations during the late Middle Pleistocene are discussed.